2003
DOI: 10.1101/gad.1048903
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1is regulated by tissue-specific forkhead proteins through a common Sonic hedgehog-responsive enhancer

Abstract: Haploinsufficiency of Tbx1 is likely a major determinant of cardiac and craniofacial birth defects associated with DiGeorge syndrome. Although mice deficient in Tbx1 exhibit pharyngeal and aortic arch defects, the developmental program and mechanisms through which Tbx1 functions are relatively unknown. We identified a single cis-element upstream of Tbx1 that recognized winged helix/forkhead box (Fox)-containing transcription factors and was essential for regulation of Tbx1 transcription in the pharyngeal endod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
216
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(232 citation statements)
references
References 49 publications
12
216
1
3
Order By: Relevance
“…Because Shh and Foxa2 have been shown to be required for tissue specific Tbx1 expression in the pharyngeal endoderm and head mesenchyme (Yamagishi et al, 2003), we examined their expression after the implantation of RA-beads. Neither Shh nor Foxa2 was down-regulated in the pharyngeal endoderm or head mesenchyme, and two further pieces of evidence suggest that it is unlikely that the RA repression of Tbx1 in pharyngeal endoderm is mediated by a decrease in expression of Shh or Foxa2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because Shh and Foxa2 have been shown to be required for tissue specific Tbx1 expression in the pharyngeal endoderm and head mesenchyme (Yamagishi et al, 2003), we examined their expression after the implantation of RA-beads. Neither Shh nor Foxa2 was down-regulated in the pharyngeal endoderm or head mesenchyme, and two further pieces of evidence suggest that it is unlikely that the RA repression of Tbx1 in pharyngeal endoderm is mediated by a decrease in expression of Shh or Foxa2.…”
Section: Discussionmentioning
confidence: 99%
“…The program predicted two RAREs in a region 600 bp upstream of Tbx1 in human and rat, and one in mouse. Whether these sites are of biological significance remains to be seen, because previous studies have demonstrated that some Tbx1 control elements and evolutionary conserved sequences are located many kilobases from the coding sequence (Yamagishi et al, 2003;Brown et al, 2004). Thus, dissection of the sites responsible for RA-mediated repression of Tbx1 could be quite difficult but might be achieved through manipulation of BACs (recombineering) (Testa et al, 2003) to produce the many reporter constructs likely to be required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Commonly, the clinical phenotype of individuals with GATA6 mutations involves the OFT, but is distinct from that of DiGeorge/22q11.2 deletion syndrome and, rather, manifests as non-syndromic CHD. To date, no molecular link has been demonstrated between GATA6 and TBX1, 8,9 however, a recent study showed that the expression of Sema3c in the OFT was downregulated in mouse embryos deficient for Tbx1, 10 suggesting that GATA6 may share, at least in part, a common molecular pathway with TBX1 during OFT development.…”
mentioning
confidence: 99%